Potential carbon sequestration across Szentendre Island - Nel, Lyndré; Masoudi, Malihe (TÁJÖKOLÓGIAI LAPOK, 2020)
Land-use in Hungarian landscapes have generally seen a decrease in agricultural land and increases in uncultivated land cover and forestry. Such types of land-use change have a cumulative impact on the atmospheric carbon that can potentially be sequestered across a landscape. The transformation of natural vegetation into cultivated land-use types and cultivated into uncultivated types alter the operationality of soil carbon storage across a time scale. This study looks at the land-use change and soil carbon storage potential, as an ecosystem service, on the Szentendre Island (59 km2) in the Danube River, Hungary, in 1998 and 2018. Land-use and land-cover (LULC) and topsoil carbon storage in 1998 and 2018 were mapped with the InVEST (Integrated Valuation of Ecosystem Services and Trade-offs) Carbon Storage and Sequestration Model. Current LULC data were matched with carbon pool data as inputs for the Carbon Model. The resulting maps present the potential carbon storage value of landuse types across the Island for 1998 and 2018. Over 20 years, Szentendre Island experienced changes in LULC; an increase in artificial surfaces, forests, and pastures, and a decrease in arable land, natural vegetation, and wetlands. Based on the land-use data, our result showed that potentially 736.97 Mg of carbon was stored in the topsoil (0–20 cm) of the Szentendre Island in 1998, compared to 737.33 Mg of carbon in 2018. In conclusion, consideration is given to the land-use change trends and the need for environmental impact assessments and programs that increase soil carbon storage for the highest level of potential carbon sequestration on Szentendre Island.